Nano-intrinsic security primitives with redox-based resistive memory - Kim, Jeeson (Frontiers in Communications and Networks, 2022)
Physical unclonable function (PUF) exploits advantages of otherwise undesirable non-idealities to create physical systems that are difficult to copy even with the same manufacturing process. Nano-intrinsic PUFs use the variability of nanotechnology per hardware instance as a source of cryptographic randomness. Among various emerging memories, redox-based resistive memory (ReRAM) is a promising candidate for providing next-generation low-cost, low-power, ultra-small PUF-based security solutions. The review shows various ReRAM-based PUF implementations and their key features. We compare their performance and discuss which properties of ReRAM to pay attention to for effective PUF implementation.